TSST-1 protein exerts indirect effect on platelet activation and apoptosis. (3rd October 2022) - Guo, Min; Yi, Tiantian; Wang, Qian; Wang, Daqing; Feng, Ping; Kesheng, Dai; Chunyan, He
Abstract: Thrombocytopenia or platelet dysfunction is a risk factor for severe infection. Staphylococcus aureus ( S. aureus ) releases a variety of virulence factors especially toxic shock syndrome toxin 1 (TSST-1), which may cause toxic shock syndrome. S. aureus, when carrying the tst gene, is more prone to cause toxic shock syndrome and is responsible for an especially high rate of mortality. However, the effect of TSST-1 protein on platelets is unknown. Patients with the tst gene positive S. aureus bacteremia showed more serious infection, higher mortality and lower platelet count. The tst gene positive S. aureus strains induce more platelet apoptosis and activation and corresponding up-regulation of Bak and down-regulation of Bcl-XL in addition to the activation of Caspase-3. C57BL/6 mice infected with the tst gene positive strains resulted in both a decrease in platelet count and an increase in platelet apoptosis and/or activation events and mortality. Moreover, TSST-1 protein, encoded by tst gene, caused the decrease of platelet count, the increase of platelet apoptosis and activation events and the level of inflammatory cytokines in vivo . However, TSST-1 protein was unable to induce traditional activation and apoptosis on human platelets in vitro . These results suggested that TSST-1 protein may exert indirect effects on platelet activation and apoptosis in vivo .